The impact of boredom on the attitudes and behaviours of edutourists during the era of COVID-19 and the mediating role of psychological distress - Afellat, Fatima Zahrae; Abdalla, Moh'd Juma; Alipour, Habib (Elsevier, 2021)
This research examined the effects of boredom on the attitudes and behaviours of international students and their indirect psychological impact during the COVID-19 pandemic. A partial least square method (PLS-SEM) was used to analyse the data taken from a sample of 260 students. As a result of this research, a significant negative effect of boredom on edutourists' attitudes as well as an insignificant positive effect on their behaviours was determined; furthermore, the students' attitudes did not affect their behaviours. A positive connection between boredom and psychological distress was significant. Additionally, results demonstrated that psychological distress did not mediate the aforementioned relationships. Nevertheless, the results of the multi-group analysis unearthed different responses among male and female students during the COVID-19. The study provides practical and theoretical implications, limitations, and areas for further research.
Keywords: COVID-19; Edutourists; Edutourism; Boredom; Psychological distress; Edutourist attitude; Edutourist behaviour